2010
DOI: 10.1152/ajpheart.00735.2009
|View full text |Cite
|
Sign up to set email alerts
|

Kinin B1receptor upregulation by angiotensin II and endothelin-1 in rat vascular smooth muscle cells: receptors and mechanisms

Abstract: Oxidative stress upregulates the kinin B(1) receptor (B(1)R) in diabetes and hypertension. Since angiotensin II (ANG II) and endothelin-1 (ET-1) are increased in these disorders, this study aims at determining the role of these two prooxidative peptides in B(1)R expression in rat vascular smooth muscle cells (VSMC). In the A10 cell line and aortic VSMC, ANG II enhanced B(1)R protein expression in a concentration- and time-dependent manner (maximal at 1 μM and 6 h). In A10 cells, ANG II (1 μM) also increased B(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 39 publications
1
21
0
1
Order By: Relevance
“…*P Ͻ 0.05, **P Ͻ 0.01 vs. vehicle. induced ERK activation, published previously by our group (26), and has been reported as optimal to study AII-induced protein expression in cultured VSMC (13,24). No significant changes in any integrin messages, including ␣ 1 -, ␣ 5 -, or ␤ 1 -integrin subunits, were detected in VSMC treated with AII compared with vehicle-treated cells (not shown).…”
Section: Vsmc Proliferation and Aii-induced Erk Activation Are Dependsupporting
confidence: 56%
“…*P Ͻ 0.05, **P Ͻ 0.01 vs. vehicle. induced ERK activation, published previously by our group (26), and has been reported as optimal to study AII-induced protein expression in cultured VSMC (13,24). No significant changes in any integrin messages, including ␣ 1 -, ␣ 5 -, or ␤ 1 -integrin subunits, were detected in VSMC treated with AII compared with vehicle-treated cells (not shown).…”
Section: Vsmc Proliferation and Aii-induced Erk Activation Are Dependsupporting
confidence: 56%
“…B2R is constitutively expressed in most tissues, including all segments of the kidney, and it mediates the majority of the physiological effects of kinins in health. In contrast, B1R is expressed at only low levels under physiological conditions, but its expression is induced by various pathological stimuli such as ischemia-reperfusion injury (50), proinflammatory cytokines (51,52), diabetes (53), bacterial endotoxins (54), and angiotensin II (55), implying an important role of B1R activation under pathological situations. The cytokine-induced upregulation of B1R is mainly regulated by mitogen-activated protein kinase (MAPK) and nuclear factor-kappa B (NF-κB) (51,56,57).…”
Section: Kinin Receptors In Diabetic Nephropathymentioning
confidence: 99%
“…In experimental studies this ET-1 effect was blocked by the ET-A-receptor antagonist, a specific inhibitor of the IkappaB-alpha-degrading proteasome complex and also prevented NF-kappa B activation thus demonstrating the ability of ET-1 to activate inflammatory pathways in human macrophages[36]. .Previous studies have also demonstrated that ET A receptor antagonist block the effect of endothelin-1 on kinin B 1 receptor expression which is associated with oxidative stress[37]. Thus blocking the inflammatory process and oxidative stress may be a potential mechanism contributing to the attenuation of plaque progression with ET A receptor antagonism in the study.…”
Section: Discussionmentioning
confidence: 95%